The behavioural intention of investors to use Islamic banking’s Investment Account Platform (IAP) as a source of investment portfolio: A structural equation modeling approach - Mohd Thas Thaker, Mohamed Asmy; Mohd Thas Thaker, Hassanudin Bin (Islamic Economic and Finance Department, Bank Indonesia, 2017)
As an alternative source of financing, Investment Account Platform (IAP) becomes a new phenomenon of raising financing for SMEs from a large pool of investors via the internet, and investment diversification portfolio tools among investors in Malaysia. The purpose of this study is to identify critical factors that influence behavioral intention of investors to invest in IAP’s projects in Malaysia. The primary data (n=1000 respondents) are collected from the investors in the Klang Valley, Malaysia and the analysis is conducted using Structural Equation Modeling (SEM). Furthermore, the model has validated its acceptance in the field by adopting the Technology Acceptance Model (TAM). This study has revealed that both the perceived usefulness and perceived easy to use are found to have a positive impact on the behavioral intention of investors to use IAP in Malaysia. Furthermore, perceived easy to use has a positive relationship and direct effect with perceived usefulness of investors to use IAP.